El juego y la motricidad gruesa en las niñas de 4 a 5 años de la unidad educativa fiscomisional La Inmaculada ubicada en la ciudad de Loja, en el período 2019 – 2020 - Cabrera Banda, Josselyn Daniela (2021)
The present research work entitled THE GAME AND GROSS MOTOR IN GIRLS 4 TO 5 YEARS OF THE EDUCATIONAL UNIT FISCOMISIONAL LA INMACULADA LOCATED IN THE LOJA CITY, IN THE PERIOD 2019 - 2020. Had as general objective to analyze the importance of games in gross motor skills in girls from 4 to 5 years, where the sample was of 18 peoples, that is, 17 girls and one teacher for the study, non-experimental research design was used with a mixed approach, using the methods: descriptive, analyticsynthetic and inductive-deductive, immersed in all the research. In addition, to get information about the variables, the interview of the classroom teacher was applied as an technique and as an instrument the Abbreviated Development Scale (EAD-1) by Nelson Ortiz, whit which it was possible to confirm that not girl reached the high level in gross motor skills, showing that most of the sample, which corresponds to 59%, is placed in a medium level, presenting difficulties to make jumps with one and two feet, alternating feet, high jumps, rebound and catch the ball. In view of the existing problem, a proposal was designed with games to strengthen gross motor skills, in which it covers different types of striking children`s games according to the age of the child, allowing him to improve the development of this area and in turn, have a better development.